Geoconservation and education for sustainability: an example based in three portuguese protected areas - Brilha, J. B. (2005)
The work done in three Portuguese protected areas followed a similar methodology: 1. Identification and characterisation of geosites with didactic relevance; 2. Development of educational strategies; 3. Production of materials such as guidebooks, leaflets, and web pages. This work allows an increase of geology awareness, not only of general public and schools but also of park managers. These examples should be enlarged to other protected areas as part of a national strategy for the education towards sustainability.